EKSISTENSI TARI JEPIN TALI BINTANG DI KOTA PONTIANAK KALIMANTAN BARAT - Yuliza Asri; Ismunandar Ismunandar; Winda Istiandini (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis research aims to describe the existence of the Jepin Tali Bintang Dance. The topic of this research is related to the development of the Jepin Tali Bintang Dance from the beginning of its creator until it can survive today and describes the factors that influence the development of the Jepin Tali Bintang Dance. The research method used was a descriptive method in the form of qualitative research is employed in this research by using a historical approach and performing several steps, namely heuristics, criticism, interpretation, and historiography. Sources of data are obtained by observation, interviews, and documentation. The technique of testing the validity of the data is using extended observations, triangulation of data sources. The Jepin Tali Bintang Dance is one of the dances originating from the Kubu kingdom, which is located in Kubu Raya Regency. This dance entered and developed in the 18th century ranging from 1930 to 1940. At first, this dance was only performed from people's homes to other residents' homes, but over time this dance was introduced to the wider community and this dance began to be performed at big events such as Pontianak City Anniversary and Culmination Point Festival. From 1930 to 2021, the Jepin Tali Bintang dance still exists in the community and the Art Performance Education campus.Keywords: Existance, Jepin Tali Bintang Dance